The Value of Administered Protection: A Capital Market Approach - Hartigan, James C.; Perry, Philip R.; Kamma, Sreenivas (The Review of Economics and Statistics, 1986)
The focus of this paper i s on the escape clause petitions filed under the Trade Act of 1974 (Section 201). First, the capital marketevent study method is used to analyze the effects of protection decisions. Then, cross-section regressions are performed to examine the influence of key variables on the observed market reaction. The authors conc lude that while protection is beneficial to beleaguered industries, the extent o f such benefits is quite narrowly circumscribed and is conditional on internal v ariables for each firm. Protection is thus not the panacea that its advocates cl aim. Copyright 1986 by MIT Press.